Игра: [роман] / Леона Дикин ; перевод с английского У. Сапциной - Дикин Леона (Серия "Смертельная угроза", 2020)
Экземпляры: ЦБ (20230508) / Инвентарный номер: 57083 / Цена: 403.15 / Сис.шифр: 84(4/8) / Авт.знак: Д 45 / ГРНТИ: 17.82 / ББК: 84(4Вел)-44